Iron and Steel - Some Political Aspects of the World Manganese Situation (with Discussion) - C. K. Leith (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1927)
ManGanese is one of the minerals which is principally consumed in countries other than origin. Nearly 85 per cent. of the world's production is used by the United States, England, Germany and France, and roughly a third of the total is used by the United States alone. On the other hand, over 85 per cent. of the world production comes from Brazil, Russia, India, the Gold Coast of Africa and the Sinai Peninsula. It follows from this fact that practically all manganese moves across international boundaries in raw or alloy form, and much the larger part of this inovement is for considerable distances and is occan bornc. There is no indication that any one of the principal consuming countries can develop even approximately adequate supplies of its own. Under abnormal war conditions, with high prices and changes in metallurgical methods, only 35 per cent. of the needs of the United States was met from local sources, and under our recent tariff only 11 per cent. There are thousands of manganese deposits scattered about the world, but only a very few which can figure largely in supplying requirements on a modern scale. The known reserves, together with highly probable extensions and explorations now under way, indicate no shortage from a world standpoint for many deeades to come. The production and marketing of manganese is going steadily into fewer and stronger hands. The steel industry uses over 90 per cent. of all the manganese mined and is acquiring control of a considerable part of the production in all of the principal fields—the Germans in Nikopol, the English in India and Gold Coast, the Americans in Georgia, India, Gold Coast and Brazil. Some of the controlling companies arc of international scope. Concentration of commercial control is a notable tendency. A natural consequence is the growing uneasiness of smaller consumers the world over about their ultimate supplies and desire to know more definitely how and where manganese supplies will be controlled in the future. The sources of supply are few cnough to warrant the belief that more or less monopolistic elements of control arc not impossible.